Effectiveness of Online Learning During the Covid-19 Pandemic on Economic Subjects in High Schools - Yuntafiani Mufidatu Rahmawati; Lukman Hakim; Tri Murwaningsih (Green Publisher Indonesia, 2021)
The Covid-19 pandemic has an impact on changing learning methods from face-to-face earning to online learning. Learning ctivities that were originally carried out in schools because of the pandemic must be carried out at home. This learning method then made many teachers use various online learning media as an alternative learning method which turned out to cause many complaints from students. The application of online learning due to changes in learning methods is a phenomenon that is studied more deeply by researchers using a descriptive qualitative approach. There are three kinds of data collection techniques used in this research, namely observation, documentation, and the interview. All data obtained by the researcher were analyzed in detail, then the validity of the data was carried out using triangulation technique. The findings of this study indicate that Google Classroom learning platform is preferred by teachers over other learning platforms such as Edmodo, WhatsApp Group, Zoom.us, and Google Meet. Google Classroom learning platform is considered effective by teachers and easily accessed by students so that students can learn independently. Many learning features make it easier for teachers to create, modify, and monitor learning so that learning is more interesting, flexible, and a collection of student assignments can be known in more detail.